2014
DOI: 10.1186/1477-7819-12-153
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of a giant gastrointestinal stromal tumor of the jejunum: a case report and literature review

Abstract: A few cases of a gastrointestinal stromal tumor (GIST) of the small intestine presenting as rupture have been reported in the medical literature. We report an unusual case of a large GIST of the jejunum that presented as a spontaneous rupture. A 70-year-old man was referred to our hospital because of fever and abdominal pain. An abdominal enhanced computed tomography (CT) scan detected a 10-cm tumor with heterogeneous staining, suggesting necrosis or abscess inside the tumor. The patient was treated with antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…A large number of in ammatory packages are seen on the edge of the tumor, suggesting that chronic in ammation is caused by repeated stimulation. For example, Chen et al [12] and Misawa S et al [13] reported the appearance of necrotic ulcers or abscesses in GIST. The tumor was large and had acute in ammation symptoms, which was inconsistent with the persistence of repeated chronic in ammation in this case.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of in ammatory packages are seen on the edge of the tumor, suggesting that chronic in ammation is caused by repeated stimulation. For example, Chen et al [12] and Misawa S et al [13] reported the appearance of necrotic ulcers or abscesses in GIST. The tumor was large and had acute in ammation symptoms, which was inconsistent with the persistence of repeated chronic in ammation in this case.…”
Section: Discussionmentioning
confidence: 99%
“…However GIST perforation seems to occur more frequently in the small bowel compared to other anatomic sites [35] . Our literature search revealed 21 cases of acute abdomen with diffuse or localized peritonitis caused by spontaneous perforation of small intestine GISTs ( Table 1 ) [9–29] . Two more cases are reported in the case-series of Mansour and Coll [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Few GISTs manifest as abdominal emergencies, such as GI haemorrhage, intestinal obstruction, or tumour perforation [7,8] . Although acute abdomen due to GIST perforation into the peritoneal cavity is rare, a few cases of peritonitis caused by perforation of small-intestinal GISTs have been reported in the literature [8–29] . Together with a review of the published cases, here we report a case of an elderly patient with acute abdomen due to spontaneous perforation of a GIST located in the jejunum.…”
Section: Introductionmentioning
confidence: 99%
“…Stromal tumors localized in the small intestine are rare, more growing outside and not into the lumen of the intestine. In the literature there are case descriptions of in growing GIST tumors causing intestinal obstruction or bleeding [8,9]. Tumors can occur in any part of the small intestine, and externally can grow large, being asymptomatic.…”
Section: Discussionmentioning
confidence: 99%